2015
DOI: 10.1590/0001-3765201520130074
|View full text |Cite
|
Sign up to set email alerts
|

Environmental changes during the last millennium based on multi-proxy palaeoecological records in a savanna-forest mosaic from the northernmost Brazilian Amazon region

Abstract: The environmental changes and the dynamics of the savanna-forest mosaic, over the last 1050 years, have been reconstructed by pollen, charcoal, radiocarbon dating mineralogical and geochemical analyses of sediment cores taken from three different Mauritia flexuosa palm swamps in the northernmost part of the Brazilian Amazon region (northern state of Roraima). Studies on the relationship between the modern pollen rain and the regional vegetation provide additional information for the interpretation of the fossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…), human‐ignited fire has markedly influenced the boundaries between forest and savanna areas, killing pioneer forest species invading savanna areas and hence hampering forest expansion (Meneses et al. ). Conversely, an expansion of forests was reported in certain areas of the state after 200 cal yr BP, allegedly because of the decline and displacement of indigenous populations after the arrival of European settlers and consequent reduction in fire occurrence (Meneses et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…), human‐ignited fire has markedly influenced the boundaries between forest and savanna areas, killing pioneer forest species invading savanna areas and hence hampering forest expansion (Meneses et al. ). Conversely, an expansion of forests was reported in certain areas of the state after 200 cal yr BP, allegedly because of the decline and displacement of indigenous populations after the arrival of European settlers and consequent reduction in fire occurrence (Meneses et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the analysis of charcoal concentrations of surface sediments in the forest–savanna transition of this region indicated that forest cover acted as an effective buffer during the last millennium, blocking fire entrance into forested ecosystems (Meneses et al. ). As in other parts of Amazonia, forest fires were probably a rare event in Roraima before the 20 th century (Schroeder et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charcoal pieces from wood found in the studied records suggested that fire contributed with the vegetation changes observed. A more complex picture was recently presented by Meneses et al (2015) in the same region, where three late-Holocene Palaeoecological records exhibited different trends: forest reduction in one place and more stable forest/palm swamp patches in the others. These findings stress the role of human-made fires in shaping savanna/ palm swamps/forest mosaics, but also point out the importance of the extremely poor, acidic soils present in the region, and local edaphic and microclimatic variations, as significant controls on the current vegetation patterns.…”
Section: Comparison With Other Savanna Records In Northern South Americamentioning
confidence: 80%
“…In a very interesting study, Maria E.N.S. Meneses and colleagues have analyzed the environmental changes for over 1000 years of the Amazon forest located in the state of Roraima (Meneses et al 2015). Using multiple lines of evidence such as geochemistry and palinological data from three different sediment cores, these authors were able to establish the vegetation dynamic in the last millennium in this region, providing some explanations on how the current sharp boundaries between the forest and savanna ecosystems have been maintained.…”
mentioning
confidence: 99%